2017
DOI: 10.1016/j.cellimm.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of extracellular matrix and leukocytes in lung inflammation

Abstract: During inflammation, leukocytes influx into lung compartments and interact with extracellular matrix (ECM). Two ECM components, versican and hyaluronan, increase in a range of lung diseases. The interaction of leukocytes with these ECM components controls leukocyte retention and accumulation, proliferation, migration, differentiation, and activation as part of the inflammatory phase of lung disease. In addition, bronchial epithelial cells from asthmatic children co-cultured with human lung fibroblasts generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
79
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 258 publications
(281 reference statements)
3
79
0
Order By: Relevance
“…In present study, we demonstrated that both RP11‐714G18.1 and LRP2BP could suppress vascular cell migration through downregulation of MMP1 expression. MMP1, also known as interstitial collagenase, is a major member of the MMP family that can facilitate vascular cell migration via degrading extracellular matrix components . It is believed to be closely associated with the vulnerability of atherosclerotic plaques as well as the risk of acute coronary syndromes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In present study, we demonstrated that both RP11‐714G18.1 and LRP2BP could suppress vascular cell migration through downregulation of MMP1 expression. MMP1, also known as interstitial collagenase, is a major member of the MMP family that can facilitate vascular cell migration via degrading extracellular matrix components . It is believed to be closely associated with the vulnerability of atherosclerotic plaques as well as the risk of acute coronary syndromes .…”
Section: Discussionmentioning
confidence: 99%
“…MMP1, also known as interstitial collagenase, 31 is a major member of the MMP family that can facilitate vascular cell migration via degrading extracellular matrix components. [32][33][34] It is believed to be closely associated with the vulnerability of atherosclerotic plaques as well as the risk of acute coronary syndromes. 35,36 Moreover, overexpression of MMP1 was detected in the shoulder region of the plaque, which seemed to be the area prone to rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Also relevant to the pathology of muscular dystrophy, is that versican and ADAMTS versicanases have been implicated in regulating inflammation in various disease models [28][29][30]. A carefully regulated inflammatory response is necessary for effective regenerative myogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…MMP10 gene expression is upregulated in airway epithelial cells infected with rhinovirus and respiratory syncytial virus . MMP10 may drive the conversion of pro‐inflammatory M1‐biased macrophages toward immunosuppressive M2‐biased cells, and, in the context of airway remodeling, MMP‐10 also controls the activation of ECM‐degrading activity in M2 macrophages …”
Section: Discussionmentioning
confidence: 99%